The technique of television interviewing - Connop, Cynthia1.; Halliday, Eric. (North Ryde, NSW. : Australian Film Television & Radio School, 1986)
The program talks on the art and skill of interviewing especially on current affairs.
Keywords: Interviewing in television; Talk shows; Reporter films and programs